West Nile Virus Survey of Birds, Horses, and Mosquitoes of the Pacific Coast, Southern Mexico - Cortés Guzmán, Antonio Juan; Sánchez Casas, Rosa María; Ibarra Juárez, Luis Arturo; Ortega Morales, Aldo Iván; García Rejón, Julián Everardo; Contreras Cordero, Juan Francisco; Mis Ávila, Pedro; Domínguez Galera, Marco Antonio; Rebollar Téllez, Eduardo Alfonso; Medina de la Garza, Carlos Eduardo; Fernández Salas, Ildefonso (Southwestern Entomologist, 2013)
Abstract. Serology of West Nile virus vectors and non-human reservoirs was surveyed at Acapulco, Jose Azueta, and Ometepec, three Pacific Coast localities of Guerrero State, Mexico. The objectives of this study were to use enzyme-linked immnosorbent assay (ELISA) to assess West Nile virus antibodies of bird and equine serum samples and use reverse transcription of polymerase chain reaction (RT-PCR) to detect the virus in field-collected resting mosquitoes. Forty birds trapped using mist nets yielded 10% seroprevalence. Similarly, 18.6% of 102 equine blood samples had West Nile virus. In addition, 4,854 mosquitoes were caught using motorized backpack aspirators and grouped into 116 pools. Of the 16 species and seven genera, no mosquito was positive for West Nile virus. Our study demonstrated West Nile virus seroprevalence on resident birds and equines in Guerrero State, Mexico.